Virtue Ethics and Education from Late Antiquity to the Eighteenth Century - Hellerstedt, Andreas (Knowledge Communities, 2018)
This book argues that premodern societies were characterized by the quest for "virtue." The concept of virtue, complicated and much fought-over, permeated society, encouraging wisdom, courage, and justice, while simultaneously legitimizing social hierarchies based on sex and nationality. By examining pedagogical texts, rituals, performances, and images, this book illuminates the evolution of virtue through time, helping readers understand the guiding principles of historical action.